Motif Cerita Rakyat Putri Pinang Masak dan Roro Jonggrang: Kajian Sastra Bandingan Model Stith Thompson - Astuty, Astuty; Dewi, Liana Sinta; Fitriyani, Chintia Rosida (Kajian Bahasa dan Sastra (KABASTRA), 2024)
Cultural context cannot be separated from society. Today the existence of folklore is growing. Starting from the development of technology, entertainment media and communication media. Each region has an undocumented oral cultural richness. Sometimes folklore develops only in its native area and is less developed in other areas. Thus, the preservation of folklore is necessary to preserve and disseminate the values to the next generation. Many folktales that develop in various regions often bring up similarities, one of which is the similarity of story motifs. The similarity of folklore motifs can be seen in the folklore of Roro Jonggrang with the folklore of Putri Pinang Masak about the rejection of a love story that results in disappointment and anger of the main character. This study aims to find motifs contained in the folklore of Putri Pinang Masak and Roro Jonggrang. An element of the story consists of several motives depending on the point of view in considering the motives. This research is a research using qualitative methods. Research methods applied to analyze motifs in the folklore of Putri Pinang Masak and Roro Jonggrang. Comparison of folklore motifs using the model of Stith Thompson on the Folklore of Putri Pinang Masak and Roro Jonggrang found 35 motifs. The data consists of: 13 similarity motifs & 7 Putri Pinang Masak folklore motifs and 15 different Roro Jonggrang folklore motifs.